Severe Raynaud's phenomenon from ethosuximide raised concern over possible onset of systemic vasculitis: a case report - Lillemor Berntson; Gunnar Liminga (BMC, 2022)
Abstract Background Ethosuximide and other anti-epileptic drugs have been reported to cause idiosyncratic reactions such as lupus-like syndromes, with elevated antinuclear antibody (ANA) levels. Herein, we present a case of a girl who developed a very severe Raynaud's phenomenon reaction and anti-Scl-70 antibodies related to treatment with ethosuximide, due to juvenile absence epilepsy (JAE). Case presentation A 12-year-old girl was diagnosed with JAE and treatment with ethosuximide was initiated. Two and a half months later her fingers, digits II-V bilaterally, began to ache and were discolored, alternatingly white, blue, or normal-colored. Two weeks later, her fingers were bluish-black, aching severely, almost continuously. The family sought medical advice. Ethosuximide was halted and due to the severe symptoms, treatment with both prednisolone and intravenous iloprost was commenced. Laboratory tests revealed high ANA levels with anti-Scl-70 pattern and confirmed anti-Scl-70 antibodies. After a few weeks, she started to improve and the symptoms slowly decreased over five months. Anti-Scl-70 was still detectable four months after onset of symptoms, though she was much improved. After eleven months, repeated ANA analyses were completely negative. Conclusion Although extremely rare, it is important to recognize that severe Raynaud's phenomenon, threatening peripheral digital circulation, may occur as an idiosyncratic reaction to ethosuximide, raising concern over possible onset of vasculitis.